Review of commonly used age based weight estimates for paediatric drug dosing in relation to the pharmacokinetic properties of resuscitation drugs. (24th May 2012) - Carasco, C; Fletcher, P; Maconochie, I
Abstract : Aim: To study which weight estimate calculation used in paediatric resuscitation results in optimal drug dosing, the calculations comprising of the three new Advanced Paediatric and Life Support (APLS) age based formulae or the UK Resuscitation Council age based formula. Method: Commonly used drugs used in paediatric resuscitation were selected and a literature search conducted for each drug's pharmacokinetic properties, concentrating on the volume of distribution derived from its hydrophilic and hydrophobic properties and their relationship to body composition. Estimates of Actual Body Weight (ABW) to Ideal Body Weight (IBW) compared and, ABW estimates were calculated using both UK Resuscitation Council and APLS formulae. Hydrophobic drugs have a higher volume of distribution than hydrophilic drugs as they distribute preferentially to Fat Mass (FM). The larger the volume of distribution, the higher the initial dose required to achieve therapeutic plasma concentrations. ABW estimates are a good indicator of volume of distribution for hydrophobic drugs as it correlates well with FM. IBW estimates may be a better indicator of volume of distribution than ABW for hydrophilic drugs, as it correlates better with Lean Body Mass. This highlights potential variation between ABW and IBW which may result in toxic or sub-therapeutic dosing. Results: The new APLS formulae, gives higher estimates of expected weight for a wider age range. This may be a more accurate reflection of ABW, than the UK Resuscitation Council, due to an increasing prevalence of obesity in children. The UK Resuscitation Council's formula appears to result in a lower estimate of weight, which may relate more closely to IBW than ABW. Conclusion: The main drugs used in paediatric resuscitation are hydrophilic, thus the APLS formulae may result in too much being given. Therefore the UK Resuscitation Council's single formula may be preferred. In addition the single formula is simple and easy to remember so may minimise error in the context of a child of unknown weight that requires administration of emergency resuscitation drugs.